2008
DOI: 10.1080/11038120802087626
|View full text |Cite
|
Sign up to set email alerts
|

Relevance and focal view point in occupational therapists’ documentation in patient case records

Abstract: The Code of ethics for occupational therapists stipulates how occupational therapists should think about the profession's central concepts in practice, where "Activity" and "Health" are two such concepts. Other guiding principles for practice are the Occupational Therapy Process Model and the ARTUR Case Record Structure. The aim of this study was to identify and describe how occupational therapists at a hospital in Sweden accomplished documentation of occupational therapy cases in patient case records. A strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…This may be due to occupational therapists adjusting their documentation by using medical language to be more respected in the multi-disciplinary team, and omitting the language of occupation and occupational performance 11 . In contrast to this, a second Swedish study found that although few occupational therapy records were complete, the majority captured activity and participation 37 . A United Kingdom review of the occupational therapy service within a National Health Service Trust likewise found that records focussed on activities of daily living 38 (an aspect of activity and participation).…”
Section: Discussionmentioning
confidence: 91%
“…This may be due to occupational therapists adjusting their documentation by using medical language to be more respected in the multi-disciplinary team, and omitting the language of occupation and occupational performance 11 . In contrast to this, a second Swedish study found that although few occupational therapy records were complete, the majority captured activity and participation 37 . A United Kingdom review of the occupational therapy service within a National Health Service Trust likewise found that records focussed on activities of daily living 38 (an aspect of activity and participation).…”
Section: Discussionmentioning
confidence: 91%